ANALISIS PUISI CHAIRIL ANWAR "DERAI-DERAI CEMARA" DENGAN PENDEKATAN MIMETIK - Syaniah Nurhalimah; Riana Dwi Lestari; Ika Mustika (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
AbstractLiterary work is an essay that evokes feelings, experiences and fantasies which are poured into writing using beautiful and interesting language. Poetry is a work of fiction with many areas of special or implied meanings that can attract writing lovers. Often poetry is analogous to other expressions so that the meaning is difficult to apply, poetry poetry has an implied meaning. Therefore, the researcher was interested in conducting a study of Chairil Anwar's work entitled "Derai-Derai Cemara" with a mimetic approach. There are many words or diction that are difficult to interpret, first the poem "Derai-Derai Cemara" reflects or mimics human life with pine trees. This poetry is dissected using a mimetic approach, which is to examine the relationship between facts or imitations in literary works. The research objective was to determine the implied meaning content and the extent to which it was related to the realities of life that the author lived. This research method uses qualitative methods that describe or describe the contents of the poetry. This study interprets and tries to understand the meaning of the natural aspects contained in the poem "Derai-Derai Cemara" by Chairil Anwar. So that the meaning implied in the poem can be clearly described.